Binary flux-promoted formation of trigonal ZnIn2S4 layered crystals using ZnS-containing industrial waste and their photocatalytic performance for H2 production. Issue 16 (25th July 2018) - Hojamberdiev, Mirabbos; Cai, Yanfei; Vequizo, Junie Jhon M.; Khan, Mohammad Mansoob; Vargas, Ronald; Yubuta, Kunio; Yamakata, Akira; Teshima, Katsuya; Hasegawa, Masashi
Abstract : Trigonal ZnIn2 S4 layered crystals were grown by a binary flux method using ZnS-containing industrial waste. Abstract : The accumulation of solid waste due to rapid industrialization has a negative impact on the environment. In this study, ZnS-containing waste from the mining-metallurgy industry was utilized for the synthesis of trigonal ZnIn2 S4 layered crystals by a flux method using various binary fluxes: CaCl2 : InCl3, SrCl2 : InCl3, BaCl2 : InCl3, NaCl : InCl3, KCl : InCl3, and CsCl : InCl3 . Among the binary fluxes used, KCl : InCl3 was found to be the most favorable for the synthesis of phase-pure trigonal ZnIn2 S4 layered crystals. The XRD and SEM results revealed that the flux-grown ZnIn2 S4 crystals have a trigonal structure and a morphology composed of large stacked layers. Unexpectedly, the UV-vis diffuse reflectance spectrum exhibited the onset of the absorption edge at approximately 700 nm for trigonal ZnIn2 S4 crystals. The photocatalytic activities for H2 production of the Pt-photodeposited ZnIn2 S4 samples grown using CaCl2 : InCl3, NaCl : InCl3, and KCl : InCl3 fluxes were evaluated. Trigonal ZnIn2 S4 crystals grown using the KCl : InCl3 flux in this study exhibited higher photocatalytic activity for H2 evolution (132 μmol h −1 ) than previously reported hexagonal ZnIn2 S4 synthesized by a hydrothermal method due to the decreased defect density and higher crystallinity achieved by the binary flux method. The presence of secondary crystalline phases (ZnS and In2 S3 ) in ZnIn2 S4 crystals grown using NaCl : InCl3 and CaCl2 : InCl3 fluxes positively impacted the photocatalytic activity and exhibited photocatalytic H2 evolution rates of 188 and 232 μmol h −1, respectively, because of the efficient separation and transfer of photogenerated charge carriers. The decay of the transient absorption of electrons in three samples at 2000 cm −1 was monitored by transient absorption spectroscopy, confirming that the lifetime of free electrons becomes longer depending on the binary flux used: KCl : InCl3 < NaCl : InCl3 < CaCl2 : InCl3 . The binary flux method applied in this study demonstrates that accumulated solid industrial wastes can be turned into beneficial photocatalytic materials.